2022
DOI: 10.1016/j.jretconser.2022.102948
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of panic buying behaviour amidst COVID-19 pandemic: The role of perceived scarcity and anticipated regret

Abstract: Panic buying behaviour is inherently undesirable due to its detrimental impact on community's resources and disruptions to supply chain systems. The prevailing COVID-19 pandemic has seen a resurgence of this phenomenon across the world, leaving supermarkets in stockout situations. While panic buying is largely reasoned as a psychological reaction to an extreme event, it is also a socially relevant behaviour as our perception of a crisis can be shaped by our observations and interactions within the society. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 67 publications
3
41
0
Order By: Relevance
“…The COVID-19 has caused great obstacles to the global economy, resulting in serious economic recession, companies and industries closing and unemployment rate rising [ 94 ]. Therefore, the current research on panic buying is of great value for current global marketing and enterprise decision-making [ 95 ]. Reviewing previous studies, digital content payment has become a new consumption trend in China especially in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 has caused great obstacles to the global economy, resulting in serious economic recession, companies and industries closing and unemployment rate rising [ 94 ]. Therefore, the current research on panic buying is of great value for current global marketing and enterprise decision-making [ 95 ]. Reviewing previous studies, digital content payment has become a new consumption trend in China especially in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, the mediating role of anticipated regret was suggested as an explanation for consumers' competitive behavior in a scarce situation formed by marketers (Gupta and Gentry, 2019). In addition, a feeling of anticipated regret was presented in relation to panic buying in a retail environment due to the COVID-19 pandemic (Yuen et al. , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“… 2 For instance, hashtags related to COVID-19 on social media platforms caused panic buying behavior among the general public. 3 Such panic behavior led to an increase in sales of online groceries by 51.5% in the UK compared to pre-pandemic time. 4 Many people suffered from anxiety and stress due to empty shelves in supermarkets that was caused by consumer panic buying behavior during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…A considerable amount of research has investigated panic buying behavior. These studies examined where and when panic buying behavior occurs, 11 social determinants of panic buying behavior, 3 ways to prevent panic buying, 12 and effects of national culture on the extent of panic buying. 13 Although extensive research has been carried out on panic buying behavior, no single study exists that examines the role of informational experience and stimulation experience of COVID-19 CRT on panic buying behavior and how such behavior leads to psychological reactions, including the sense of security.…”
Section: Introductionmentioning
confidence: 99%